Deciphering micro-polarity inside the endoplasmic reticulum using a two-photon active solvatofluorochromic probe. Issue 75 (31st August 2018) - Pal, Kaushik; Samanta, Indranil; Gupta, Rahul Kumar; Goswami, Debabrata; Koner, Apurba Lal
Abstract : A new class of two-photon active and solvatofluorochromic dyes for the determination of ER polarity is reported. Abstract : A new class of two-photon active and solvatofluorochromic dyes for the determination of ER polarity is reported. The fluorescent colour spans almost the entire visible spectrum. One of the derivatives is rationally designed for specific ER targeting. Finally, the fluorescence spectral scanning technique has been utilised to determine the micro-polarity inside the ER which is found to be much lower than that of water.